Market Orientation Contact, And Company Working - Hakim, Chairul (Yayasan Pendidikan Belajar Berdikari, 2024)
The study seeks to explain the research gap in the causal link between market orientation and business performance. To explain the discrepancy, the research focuses on the function of the corporate business environment's variable moderator, namely corporate competitive strategy and corporate entrepreneurship. The analytical unit for this research is a small business in West Java. In this research, 231 firms were identified, however only 111 answered to the survey. MRA analysis is used to investigate the role of corporate entrepreneurship in mediating the cultural causal link between market orientation and corporate performance. Corporate entrepreneurship strengthens the effect of a market-oriented culture on company performance. Market orientation has a bigger effect on business performance as corporate entrepreneurship increases. Subgroup analysis is used to investigate how a firm's competitive strategy modifies the link between orientation and company performance. The study's findings indicate that the impact of market oriented culture on firm performance varies depending on the competitive strategy.